Techniques of Ration Formulation for Smallholder Dairy Farmers - Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra; Mekonnen, Kindu; Gebreyes, Million; Varijakshapanicker, Padmakumar (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training on Livestock Feed and Forage Innovations